Municipal Home Rule in Missouri - Henry J. Schmandt (Washington University Law Quarterly, 1953)
The chief goals of home rule have therefore been: (1) to prevent or minimize. legislative interference in matters that are primarily of local concern; (2) to permit the local communities to adopt the type and form of government they desire; (3) to provide the cities. with sufficient powers to meet the increasing needs for local services without the necessity of repeatedly seeking new authority from the legislature as they are compelled to do when the charters are legislative enactments.
Keywords: Municipal corporations; Local government